2022
DOI: 10.1002/mame.202100784
|View full text |Cite
|
Sign up to set email alerts
|

Printable Graphene Oxide Nanocomposites as Versatile Platforms for Immobilization of Functional Biomolecules

Abstract: A series of novel nanocomposites containing graphene oxide (GO) suitable for stereolithography is presented. Different loads of GO are tested, identifying that these materials can be printed with concentrations up to 2.5 wt% GO, presenting improved mechanical properties for concentrations below 1.0 wt% GO. In this range, the nanocomposites exhibit higher strength and toughness when compared to the pristine resin. Microscopic analyses of the material demonstrate that this can be correlated with the good compati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This was due to the insufficient interfacial dispersion caused by the agglomeration of L-CNCs in the methacrylate matrix, which was in accordance with many studies, where increasing the nanofiller concentration beyond its percolation threshold results in a decrease in mechanical properties. 122 After post-curing, the addition of 0.1 and 0.5 wt% L-CNCs enhanced the mechanical properties and also improved the thermal stability, as shown in Fig. 14.…”
Section: Applicationsmentioning
confidence: 91%
See 4 more Smart Citations
“…This was due to the insufficient interfacial dispersion caused by the agglomeration of L-CNCs in the methacrylate matrix, which was in accordance with many studies, where increasing the nanofiller concentration beyond its percolation threshold results in a decrease in mechanical properties. 122 After post-curing, the addition of 0.1 and 0.5 wt% L-CNCs enhanced the mechanical properties and also improved the thermal stability, as shown in Fig. 14.…”
Section: Applicationsmentioning
confidence: 91%
“…Similarly, the mechanical properties increased with thermal post-curing, as evidenced by ref. 47, 72, 82, 122, 127, 129 and 132 It was observed that the Young's modulus and yield strength in the linear regime were more rapid in graphene nanocomposites compared to the control specimens. The Young's modulus and yield strength increased from 1601 MPa and 77 MPa to 2180 MPa and 88 MPa, respectively, compared to the control specimens.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations